Concurrent 3-D Sonifications Enable the Head-Up Monitoring of Two Interrelated Aircraft Navigation Instruments. (December 2014) - Towers, John; Burgess-Limerick, Robin; Riek, Stephan
Objective: The aim of this study was to enable the head-up monitoring of two interrelated aircraft navigation instruments by developing a 3-D auditory display that encodes this navigation information within two spatially discrete sonifications. Background: Head-up monitoring of aircraft navigation information utilizing 3-D audio displays, particularly involving concurrently presented sonifications, requires additional research. Method: A flight simulator's head-down waypoint bearing and course deviation instrument readouts were conveyed to participants via a 3-D auditory display. Both readouts were separately represented by a colocated pair of continuous sounds, one fixed and the other varying in pitch, which together encoded the instrument value's deviation from the norm. Each sound pair's position in the listening space indicated the left/right parameter of its instrument's readout. Participants' accuracy in navigating a predetermined flight plan was evaluated while performing a head-up task involving the detection of visual flares in the out-of-cockpit scene. Results: The auditory display significantly improved aircraft heading and course deviation accuracy, head-up time, and flare detections. Head tracking did not improve performance by providing participants with the ability to orient potentially conflicting sounds, suggesting that the use of integrated localizing cues was successful. Conclusion: A supplementary 3-D auditory display enabled effective head-up monitoring of interrelated navigation information normally attended to through a head-down display. Application: Pilots operating aircraft, such as helicopters and unmanned aerial vehicles, may benefit from a supplementary auditory display because they navigate in two dimensions while performing head-up, out-of-aircraft, visual tasks.